Genetics and Physiology of Colicin-tolerant Mutants of Escherichia coli - de Zwaig, Rosa Nagel (1967)
A series of colicin-tolerant (tol) mutants of Escherichia coli K-12, which adsorbed colicins but were not killed by them, were isolated and studied genetically and physiologically. Three major classes of mutants were found: tol II, tolerant to colicins A, E1, E2, E3, and K; tol III, tolerant to A, E2, E3, and K; and tol VIII, tolerant to E1 only. The sites of tol II and tol III mutations mapped near the gal region (gene order: tol-gal-bio) and were cotransduced with gal by P1. In heterozygous diploids, tol(+) was dominant over tol; tol II and tol III gave full complementation. All the tol mutations that mapped near gal rendered the bacteria more fragile during growth and hypersensitive to deoxycholate and to ethylenediaminetetraacetic acid. The tol VIII mutation mapped between str and his. These mutants were extremely sensitive to deoxycholate and were also hypersensitive to methylene blue, acridines, and various other compounds. The sensitivity is attributed to increased uptake due to selective alteration of the permeability barrier. The colicin-tolerant mutations are interpreted as affecting some components of the cytoplasmic membrane which mediate between the adsorbed colicin molecules and the target sites of their biochemical effects in the bacterial cell.